2016
DOI: 10.1097/mop.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Defining neonatal sepsis

Abstract: Purpose of the review Although infection rates have modestly decreased in the neonatal intensive care unit (NICU) as a result of ongoing quality improvement measures, neonatal sepsis remains a frequent and devastating problem among hospitalized preterm neonates. Despite multiple attempts to address this unmet need, there have been minimal advances in clinical management, outcomes, and accuracy of diagnostic testing options over the last three decades. One strong contributor to a lack of medical progress is a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
226
0
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(254 citation statements)
references
References 79 publications
6
226
0
22
Order By: Relevance
“…Several patients in our study were assigned a culture‐negative EONS diagnosis and received antibiotic treatment for at least three days, despite low CRP values. A review concluded that the lack of an accepted consensus definition for neonatal sepsis impeded efforts towards improved diagnostic and prognostic options for this condition . We found some marked clinical and laboratory differences between culture‐confirmed EONS and culture‐negative EONS.…”
Section: Discussionmentioning
confidence: 81%
“…Several patients in our study were assigned a culture‐negative EONS diagnosis and received antibiotic treatment for at least three days, despite low CRP values. A review concluded that the lack of an accepted consensus definition for neonatal sepsis impeded efforts towards improved diagnostic and prognostic options for this condition . We found some marked clinical and laboratory differences between culture‐confirmed EONS and culture‐negative EONS.…”
Section: Discussionmentioning
confidence: 81%
“…El distrés respiratorio, la bradipnea y la hipotonía (79%, 52% y 40% respectivamente), fueron los síntomas más comunes entre los pacientes del estudio, lo cual es similar a lo descrito en la literatura 10 . A pesar que en los criterios diagnósticos de infección se encuentra la distermia y la taquicardia como predictores de infección neonatal 4 , en nuestro estudio las alteraciones en la frecuencia cardiaca y en la temperatura sucedieron en menos del 40% de los pacientes.…”
Section: Discussionunclassified
“…La sepsis se define como un estado de respuesta inflamatoria sistémica que se diagnostica en los recién nacidos según factores de riesgo perinatales (fiebre materna, madre con corioamionitis, ruptura prematura de membranas de más de 18 horas, pobre control prenatal) 4 , manifestaciones clínicas (distermias, taquicardia/bradicardia, taquipnea/bradipnea, alteraciones del sistema nervioso central como letargia/irritabilidad o hipotonía, distrés respiratorio, hipoperfusión) y alteraciones paraclínicas (leucocitosis o leucopenia, bandas, PCR/procalcitonina elevada, trombocitopenia) incluyendo cultivos 5 .…”
Section: Introductionunclassified
“…Neonatal sepsis is a global challenge causing high morbidity and mortality among newborns [1][2][3][4]. The global infant mortality rate in 2014 was 29 per 1000 live births-the common cause being infection [5].…”
Section: Introductionmentioning
confidence: 99%